Learning Citizenship Education in The Implementation of Character Education in The Scope of Primary Schools - Lestari, Zachwa Adinda (Berpusi Publishing, 2025)
This research is research that uses case studies by further investigating the causes of certain social aspects. The author also interviewed teachers and students at elementary schools in Buntu Pane sub-district to collect data that will be developed or proven to solve the problems in the research. The aim of this research is to look at the character education of the younger generation after the implementation of character education in citizenship education and to be able to instill good character for the life of society in the future. The current situation of the young generation in Indonesia is very worrying. Various incidents involving the younger generation are increasing, showing that there is moral damage currently carried out, shows that the younger generation no longer has good character. By because that education character very required. Wrong one way to make it happen this matter for future generations is through education citizenship. Learning education citizenship expected can renew character participant educate which the more down and align it with the values of Pancasila.